Strategic approach on N-oxides in gold catalysis: a case study - Schießl, Jasmin; Stirn, Judith; Emler, Kirsten; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2019)
An extensive kinetic study of selected key reactions of (oxidative) gold catalysis concentrates on the decrease of the catalytic activity due to inhibition of the gold(I) catalyst caused by pyridine derivatives that are obtained as by-products if N-oxides are applied as oxygen donors. The choice of the examined pyridine derivatives and their corresponding N-oxides has been made regardless of their commercial availability; particular attention has been paid to the practical benefit which up to now has been neglected in most of the reaction screenings. The test reactions were monitored by GC and 1H NMR spectroscopy. The received reaction constants provide information concerning a correlation between the electronic structure of the heterocycle and the catalytic activity. Based on the collected kinetic data, it was possible to develop a basic set of three N-oxides which have to be taken into account in further oxidative gold(I)-catalyzed reactions.